'NEW' POPULATION, NEW CHALLENGES: YOUNG ADULTS IN PALLIATIVE CARE. Issue 1 (1st March 2013) - Sivell, S; Lidstone, V; Taubert, M; Thompson, C; Nelson, A
Abstract : Introduction: The prognosis of life-limiting conditions of childhood has improved in recent years with an increase in the number of young people accessing adult specialist palliative care (SPC) services. However, little is known about the learning needs and requirements of SPC teams to help provide them with the knowledge and skills to provide care to young people. Aims and Methods: To identify the training needs of SPC teams and inform the development of an education package for SPC teams. Online Delphi Process: Collated expert opinion on the format, delivery and content of the education package.Round 1: content analysis of free text responses. Rounds 2 and 3: median and mean scores calculated to score the relevance/importance of each item. IQR scores assessed the extent of agreement about the scored relevance of each items. Items where no agreement was reached in Round 2 were put forward to Round 3 for re-rating. Focus groups: Focus groups were held with young people (pre- and post-transition), parents/carers of young people post-transition and staff from a local adult hospice and analysed using thematic analysis. Results: Delphi: Consensus was reached on the frequency of delivery, who could deliver the training, format of the package and content. Focus Groups: Discussions centred around: challenges of caring for young people; barriers to transition; education and training of staff; facilitating transition. Conclusions: Recommendations include a continuous/rolling programme of education, tailored for content and mode of delivery and incorporated into working practice. A template to guide handover and a single point of contact would facilitate the transition process.